2016
DOI: 10.3109/15368378.2016.1138124
|View full text |Cite
|
Sign up to set email alerts
|

Choice of osteoblast model critical for studying the effects of electromagnetic stimulation on osteogenesisin vitro

Abstract: The clinical benefits of electromagnetic field (EMF) therapy in enhancing osteogenesis have been acknowledged for decades, but agreement regarding the underlying mechanisms continues to be sought. Studies have shown EMFs to promote osteoblast-like cell proliferation, or contrarily, to induce differentiation and enhance mineralization. Typically these disparities have been attributed to methodological differences. The present paper argues the possibility that the chosen osteoblast model impacts stimulation outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…In line with this, Wei et al showed that exposure to f = 48 Hz ELF-PEMF promoted proliferation (increased number of cells in S and G(2)M phase) of primary rat calvaria cells but not of MC3T3-E1 cells [33], suggesting that the observed effect is strongly dependent on the differentiation status of the cells. Bique et al observed similar effects in strongly differentiated SaOs-2 cells and less differentiated MC3T3-E1 cells exposed to f = 50 Hz ELF-PEMF [34]. This finding is supported by the work of Kaivosoja et al, which showed stimulatory effects of f = 15 Hz ELF-PEMF on proliferation being more pronounced in SaOs-2 cells when compared with less differentiated mesenchymal stem cells [35].…”
Section: Elf-pemf Effects On Bone Cell Growthmentioning
confidence: 64%
“…In line with this, Wei et al showed that exposure to f = 48 Hz ELF-PEMF promoted proliferation (increased number of cells in S and G(2)M phase) of primary rat calvaria cells but not of MC3T3-E1 cells [33], suggesting that the observed effect is strongly dependent on the differentiation status of the cells. Bique et al observed similar effects in strongly differentiated SaOs-2 cells and less differentiated MC3T3-E1 cells exposed to f = 50 Hz ELF-PEMF [34]. This finding is supported by the work of Kaivosoja et al, which showed stimulatory effects of f = 15 Hz ELF-PEMF on proliferation being more pronounced in SaOs-2 cells when compared with less differentiated mesenchymal stem cells [35].…”
Section: Elf-pemf Effects On Bone Cell Growthmentioning
confidence: 64%
“…Due to such high ion release levels, the materials synthesized need to be treated with PBS for 24 hr prior to being used with the cells in order to avoid high ion concentrations and sudden pH increases. The authors have chosen to use three osteogenic supplements with Saos‐2 in this study as have many other researchers who study the effect of different stimulus on osteogenesis and matrix production in vitro (Bique, Kaivosoja, Mikkonen, & Paulasto‐Kröckel, 2016). However, the authors have ensured that the concentration of dexamethasone was the same value for both the control and experimental groups.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we show the effects of short exposures to an Extremely Low Frequency Magnetic Field (ELF MF) on human osteosarcoma cell line SaOS-2, which is an effective and widely used in vitro model of human bone tissue [ 26 ]. SaOS-2 is a kind of osteoblast-like cell and widely used in the study of osteogenesis, expecially to analyze the effect of electromagnetic signals [ 38 , 39 ]. The wave was generated by a device recently introduced among clinical treatments of fractures or other bone diseases.…”
Section: Discussionmentioning
confidence: 99%